2017
DOI: 10.12669/pjms.333.12397
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in reducing number of acute exacerbations in Chronic Obstructive Pulmonary Disease (COPD) patients

Abstract: Background and Objective:Chronic obstructive pulmonary disease (COPD) is characterized by chronic incompletely reversible poor airflow and air trapping and usually this debilitating disorder limits the outside activities of the patients depriving them of sunlight which is a rich source of Vitamin D. The objective of this study was to determine the effect of vitamin D supplementation in reducing number of acute exacerbation in COPD patients.Methods:This randomized control trial was conducted at East Medical War… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 16 publications
0
24
0
2
Order By: Relevance
“…Recently, numerous researchers indicated that 1,25(OH) 2 D 3 , the active form of vitamin D, recovered elastaneinduced reduction of forced expiratory volume in 1 s (FEV1) to the forced vital capacity (FVC) and alveolar destruction in a mouse model of COPD (15). A population-based study found that vitamin D supplementation obviously alleviated acute exacerbation in COPD patients (16). Otherwise, experiment in vitro also found that vitamin D receptor (VDR) knock-out mice showed increased lung inflammation and accelerated lung function decline in a COPD mouse model (17).…”
mentioning
confidence: 99%
“…Recently, numerous researchers indicated that 1,25(OH) 2 D 3 , the active form of vitamin D, recovered elastaneinduced reduction of forced expiratory volume in 1 s (FEV1) to the forced vital capacity (FVC) and alveolar destruction in a mouse model of COPD (15). A population-based study found that vitamin D supplementation obviously alleviated acute exacerbation in COPD patients (16). Otherwise, experiment in vitro also found that vitamin D receptor (VDR) knock-out mice showed increased lung inflammation and accelerated lung function decline in a COPD mouse model (17).…”
mentioning
confidence: 99%
“…In terms of respiratory diseases, there is wide evidence of benefit from cholecalciferol supplementation in chronic obstructive pulmonary disease (COPD), with two RCTs demonstrating statistically significant benefits in favor of cholecalciferol in several relevant clinical end-points, such as reduced rate of exacerbations and improvement of FEV1 (forced expiratory volume in the first second) [ 37 , 38 ], as well as another RCT showing improvements in inspiratory muscle strength and maximum oxygen consumption [ 39 ]. Also noteworthy in this clinical context is the ViDiCO RCT of Martineau AR et al, performed on 240 COPD patients and published in Lancet Respiratory Medicine in 2015, in which it was observed that cholecalciferol supplementation produced a statistically significant reduction in the risk of moderate or severe exacerbation in COPD patients with baseline levels of 25(OH)D below 20 ng/mL at the start of the clinical trial [ 40 ].…”
Section: Clinical Efficacy Of Cholecalciferol and Calcifediol: Whamentioning
confidence: 99%
“…In comparison, Hornix et al performed a subgroup analysis on people with very low baseline 25(OH)D levels from Lehouck's study population, which showed positive results in improving inspiratory muscle strength [ 30 ]. Later on, many RCTs proved this vitamin to be protective of the frequency of acute exacerbations of COPD [ 31 , 33 , 34 ].…”
Section: Reviewmentioning
confidence: 99%